Comparison of the Far-Eastern Seas and North-West Pacific by integral characteristics of pelagic and benthic trawled macrofaun - Igor V. Volvenko (Известия ТИНРО)
The Bering Sea, ​​Okhotsk Sea, Japan/East Sea and adjacent waters of the Pacific Ocean (mainly within EEZ of Russia) are compared by abundance of pelagic and benthic macrofauna, its species richness, evenness, diversity, and mean weight of animals using the data of long-term large-scale pelagic and bottom trawl surveys conducted by Pacific Fish. Res. Center (TINRO) in 1977-2010.